Designing Teaching Material based-Animation Video for Teaching English language at the Elementary Level - Arimuliani Ahmad; Johari Afrizal (AL-ISHLAH: Jurnal Pendidikan, 2023)
Enhancing teaching and learning experience in elementary school is considered rucial effort nowadays. Animation videos can be an alternative to engage students in learning, encouraging their cognitive and active learning. This study aimed to show the result of validation design for animation videos as supplementary teaching material. It described the animation video design and also the validation process from experts. The instrument used was a questionnaire. The validation questionnaire was distributed to two experts, and its validation was presented by CVI (content validation Index). The result shows that the animation video was designed through five different chapters: Here My Bedroom, My Mother is a Nurse, What Day Today?, My Bike, and Let Us Do Something. Therefore, the validation result shows 0,91 CVI for Cognitive Load for a very valid category, 0,97 CVI for Students Engaging for a very valid category, and 0,82 CVI for medium validity. It assumed that these animation videos were valid to be adopted in teaching and learning English Subjects for Elementary students.